A methodological proposal for the analysis of the culture and the literary interview - Arráez-Betancort, Rosa María; Garrote-Fernández, Sonia María (Estudios sobre el Mensaje Periodístico, 2023)
Focusing on what journalists ask and the responses of authors, this work presents a methodology of content analysis applicable to the journalistic genre of the literary interview and may enrich the specialization of cultural journalism, both in its procedures reflected in the publication of literary interviews and in the gathering of knowledge that allows contextualizing and understanding literary and artistic culture, as well as the keys to current culture from a sociological perspective. In order to test and verify the methodology of analysis developed and to understand the relevance of the dimensions acquired by the literary journalistic interview, 51 interviews have been analyzed, taking advantage of the feminist claim as a cultural news event and have been broadcasted digitally in ABC and El País during the month of March 2018. To store the data associated with the study, a relational database has been designed with Microsoft Access.
Keywords: Literary interview; cultural journalism; culture; discourse analysis; Microsoft Access